The effect of traditional wet cupping therapy on (methylarginine) load: The effect of wet cupping therapy (Indian Journal of Traditional Knowledge (IJTK), 2025)
Hi-jama therapy or wet cupping therapy is a complementary therapy that has been in order to centuries in the complementary and preventive treatment of various cardiovascular, metabolic, and inflammatory disorders. However, its mechanism of action is yet not completely elucidated and further studies are needed. This study aims to add to the elucidation of the of hi-jama therapy mechanism by comparing methylarginine grades in cupping blood and intravenous blood. This study included 100 healthy women aged 20-60 years, without any chronic disease, who underwent hi-jama therapy at Konya Necmettin Erbakan University Medical Faculty Traditional and Complementary Medicine Center. Methylarginine measurement was performed as a biochemical test with the tandem mass spectrometry. It was determined that total methylarginine concentrations increased in cup blood compared to venous blood in individuals who underwent wet cupping therapy. Our findings support the hypotheses that wet cupping therapy may act through detoxification of harmful metabolites from the blood.